2007
DOI: 10.1111/j.1365-2893.2006.00825.x
|View full text |Cite
|
Sign up to set email alerts
|

No significant differences in histology and response to interferon treatment in hepatitis B carriers of genotypes C and recombinant B

Abstract: Hepatitis B virus (HBV) genotypes B and C are most prevalent in China and genotype B is found exclusively in recombination with the pre-C/C gene of genotype C. We investigated whether there is a difference in clinical relevance between the two genotypes sharing the same pre-C/C gene. Thus, we determined the genotype of HBV among consecutive HBeAg-positive patients with tailored interferon-alpha (IFN-alpha) therapy, and the demographic, baseline clinical characteristics and treatment results were compared betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…This was consistent with that of our recent report [24] and also with that of the pegylated IFNa2a trial, which studied predominantly Asians [20].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This was consistent with that of our recent report [24] and also with that of the pegylated IFNa2a trial, which studied predominantly Asians [20].…”
Section: Discussionsupporting
confidence: 93%
“…The efficacy of therapy with IFNa for chronic hepatitis B has long been established [2,3] and its long-term benefits have been indisputable [4][5][6][7]. However, the overall outcome is not entirely ideal, because meta-analyses of the results from several trials have shown that the sustained response rate is only 25-40% in HBeAg-positive patients with the traditional regimen of 10 million units (MU) three times a week for [16][17][18][19][20][21][22][23][24] weeks [3,[8][9][10]. In Chinese patients, the response is still more modest and less durable because of the immune tolerance to the virus as a result of infection occurring in early life [11].…”
Section: Introductionmentioning
confidence: 99%
“…Four studies reported the ETR between the genotype B and C groups. Among these, rates of ALT normalization and HBV DNA negative were reported in four studies, and rates of HBeAg clearance and HBeAg seroconversion were reported in three studies . For rates of ALT normalization, HBV DNA negative and HBeAg clearance, there was significant heterogeneity (Q = 12.97, P = 0.005, I 2 = 76.9%; Q = 12.23, P = 0.007, I 2 = 75.5% and Q = 4.73, P = 0.094, I 2 = 57.8%, respectively); thus, the random effects model was used.…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies involving 1855 participants (genotype B group = 802, genotype C group = 1053) reported the rate of sustained ALT normalization. Luo et al . reported two outcome data; thus, there were 10 reports of outcome data in the meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation